2018
DOI: 10.21470/1678-9741-2018-0174
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Mortality in Children with Congenital Heart Disease Delivered at a Brazilian Tertiary Center

Abstract: ObjectiveThis study aims to investigate the incidence of postnatal diagnosis of congenital heart disease (CHD) and the predictive factors for hospital mortality.MethodsThis retrospective cohort study was conducted at a Brazilian tertiary center, and data were collected from medical records with inclusion criteria defined as any newborn with CHD diagnosed in the postnatal period delivered between 2015 and 2017. Univariate and multivariate analyses were performed to determine the potential risk factors for morta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
(27 reference statements)
2
5
0
Order By: Relevance
“…Prematurity was directly related to the outcome, which agrees with the study of Rocha et al 20 It should be highlighted that the formation of the heart is complete around the eighth week of gestation 2 and that premature delivery alone is not directly related to most of the malformations. It is likely that the presence of CHD may function as a determining factor of preterm delivery, as shown by Laas and collaborators.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Prematurity was directly related to the outcome, which agrees with the study of Rocha et al 20 It should be highlighted that the formation of the heart is complete around the eighth week of gestation 2 and that premature delivery alone is not directly related to most of the malformations. It is likely that the presence of CHD may function as a determining factor of preterm delivery, as shown by Laas and collaborators.…”
Section: Discussionsupporting
confidence: 90%
“…It is likely that the presence of CHD may function as a determining factor of preterm delivery, as shown by Laas and collaborators. Regarding advanced maternal age (34-49 years of age) as a factor associated with CHDs, other studies 16,17,12,20,22 give support to our results. This can be attributed to the greater tendency of genetic alterations with consequent chromosomal syndromes in children of this mother's age group, which are usually associated with a higher incidence of CHDs, as occurs in the trisomy 21 chromosome, for example.…”
Section: Discussionsupporting
confidence: 86%
“…As described by others, the severity of CHD is an important factor affecting mortality in both term and preterm patients ( 17 , 18 ). We found severe CHD to be associated with worse outcomes, but no evidence for differences between simple and moderate CHD.…”
Section: Discussionmentioning
confidence: 77%
“…The prevalence of PEM was comparable to other studies' findings. Raissadati et al [20] found that FTT was 11.9% among children and Rocha et al [21] reported that 40% was the incidence of malnutrition. According to Latal et al [22] the incidence of malnutrition was 92% among children with CHD's in comparison to other studies [23,24].…”
Section: Discussionmentioning
confidence: 99%